2017
DOI: 10.1186/s40249-017-0253-y
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of a non-governmental organisation’s Community Based Tuberculosis Care Programme to case finding in Myanmar: trend over time

Abstract: BackgroundIt is estimated that the standard, passive case finding (PCF) strategy for detecting cases of tuberculosis (TB) in Myanmar has not been successful: 26% of cases are missing. Therefore, alternative strategies, such as active case finding (ACF) by community volunteers, have been initiated since 2011. This study aimed to assess the contribution of a Community Based TB Care Programme (CBTC) by local non-government organizations (NGOs) to TB case finding in Myanmar over 4 years.MethodsThis was a descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…We believe that the project Axshya activities resulted in changes in the case finding indicators as a result of its effect on presumptive TB sputum examination rate that could be attributed largely to two activities under the project: Axshya SAMVAD and SCT (Table 3). This in There were many studies that were without a control arm, unlike our study [29][30][31]. Hence, they were not in a position to conclusively determine the effect of the TB screening strategy [15].…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…We believe that the project Axshya activities resulted in changes in the case finding indicators as a result of its effect on presumptive TB sputum examination rate that could be attributed largely to two activities under the project: Axshya SAMVAD and SCT (Table 3). This in There were many studies that were without a control arm, unlike our study [29][30][31]. Hence, they were not in a position to conclusively determine the effect of the TB screening strategy [15].…”
Section: Resultsmentioning
confidence: 83%
“…There were many studies that were without a control arm, unlike our study [ 29 31 ]. Hence, they were not in a position to conclusively determine the effect of the TB screening strategy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large community based awareness raising and active case finding approach in India demonstrated an increase in case detection of smear positive TB by 11% in that country (Calcagno et al, 2014). Studies in Myanmar have shown that the contribution of community based ACF can vary between projects ranging from 15% to 52% but decreasing overtime from 6% to 4% (Maung et al, 2017;Soe et al, 2017). The systematic review showed that the NNS in various risk groups in high TB incidence settings (>300 cases per 100 000) ranges between 17 in household contacts to 100 in the general population (World Health Organization (WHO), 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An ACF project in Cambodia that screened household and neighbourhood contacts of historical index cases in the past 2 years show a substantial increase in case notification (Morishita et al, 2016). There are few studies demonstrating the contribution of different community-based case finding projects in Myanmar (Maung et al, 2017;Soe et al, 2017), but there is limited evidence on the effectiveness of each of these interventions. Further evaluation of ACF interventions in Myanmar is needed to establish the most efficient and effective interventions to take to scale.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to improve public health and social health, especially in times of crisis, without the help of NGOs ( 7 ). Studies have shown NGOs have fulfilled a major role in the implementation of following health programs: control of smoking ( 8 ) and infectious and epidemic diseases (for instance: media campaigns); provision of counseling and access to condoms; provision of services to vulnerable and sensitive cultural groups such as sex workers, prisoners, and immigrants who suffer from HIV / AIDS ( 9 , 10 ); prevention of malaria ( 5 );, improvement of women’s health ( 11 ); treatment of burn wounds ( 12 ); decrease in infant mortality ( 13 ); procurement of equipment, facilities, medicine, and medical supplies ( 14 ); identification of tuberculosis patients and provision of tuberculosis care ( 15 ); provision of relief and acceleration of the reconstruction process during and after earthquakes ( 16 , 17 ) waste management ( 18 , 19 ); and provision of services to mental patients ( 20 ). In this regard, the World Development Report of World Bank in 1993 called for policies on investment in health care.…”
Section: Introductionmentioning
confidence: 99%